2016
DOI: 10.4103/0259-1162.164731
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on postoperative pain relief in laparoscopic cholecystectomy: Intraperitoneal bupivacaine versus combination of bupivacaine and buprenorphine

Abstract: Context:To assess the analgesic efficacy of the combination of bupivacaine and buprenorphine in alleviating postoperative pain following laparoscopic cholecystectomy.Aims:Laparoscopic cholecystectomy is comparatively advantageous as it offers less pain in the postoperative period and requires a shorter hospital stay. There are only a few studies performed to evaluate the analgesic efficacy of intraperitoneal instillation of buprenorphine and bupivacaine during laparoscopic cholecystectomy.Settings and Design:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Furthermore, various methods have been studied to reduce PONV in these patients (34). Similar to our findings, Khurana et al reported that intraperitoneal bupivacaine reduced pain in the first 24 hours after surgery compared with the placebo group (35). Sharma et al also reported that intraperitoneal bupivacaine and ropivacaine resulted in pain relief in the first 24 hours after surgery (18).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, various methods have been studied to reduce PONV in these patients (34). Similar to our findings, Khurana et al reported that intraperitoneal bupivacaine reduced pain in the first 24 hours after surgery compared with the placebo group (35). Sharma et al also reported that intraperitoneal bupivacaine and ropivacaine resulted in pain relief in the first 24 hours after surgery (18).…”
Section: Discussionsupporting
confidence: 85%
“…This was similar to other investigations. 9,15,[17][18][19] Raetzell et al compared bupivacaine (0.125 % and 0.25 %) to normal saline and found no difference in pain scores between the groups, 20 which could be related to the lower concentration of bupivacaine utilised. Choi et al reviewed 39 random control trial reviews and concluded that intraperitoneal local anaesthetics did not significantly diminish parietal pain but had a favourable analgesic impact on visceral pain and shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] found that mean VRS score was lower in both the groups with significant difference between the VRS score in immediate postoperative period, 1 st h, 3 rd h, and then from 7 th h to 12 th h. The results were also supported by Khurana et al . [ 15 ]…”
Section: Discussionmentioning
confidence: 99%